Tinjauan Yuridis Normatif Perbandingan Peraturan Pengadaan Tanah untuk Infrastruktur Perkeretaapian antara Indonesia dengan Malaysia - Oktaria, Dhina Setyo; Wibowo, Agustinus Prasetyo Edi (Politeknik Perkeretaapian Indonesia Madiun, 2020)
Land acquisition for public purposes, including for the construction of railroad infrastructure, is a matter that is proposed by all countries in the world. The Indonesian government or the Malaysian royal government needs land for railroad infrastructure development. To realize this, a regulation was made that became the legal umbrella for the government or royal government. The people must agree to regulations that require it. Land acquisition for public use in Malaysia can be completed quickly in Indonesia. The influencing factor is the different perceptions of the understanding of what are in the public interest, history and legal systems of the two countries as well as the people's reaction from the two countries